Sustaining growth needs contextual supports: The mindset × ecological-system approach to motivation - Mantou Lou , Nigel (Studies in Second Language Learning and Teaching, 2025)
The belief that abilities can be cultivated, commonly referred to as a growth mindset, plays an important role in learners’ motivation and persistence in their educational journey, including learning a new language. Recent research suggests that having a growth mindset alone is insufficient for educational success. Rather, the “seed” of growth mindsets flourishes best when the “soil” of the environment offers students abundant opportunities to apply and implement their growth mindsets in their learning process (i.e., the mindset × context theory). However, discussions about this contextual impact, particularly within the broader sociocultural environment (akin to “climate” in the seed-and-soil metaphor) are limited in mindset research. Therefore, this article introduces the mindset × ecological-system framework by synthesizing emerging research from psychology, education, and applied linguistics, aiming to provide a more comprehensive understanding of how social and cultural factors impact the psychological dynamics of mindsets. This framework illustrates how embedded socioecological systems, ranging from interpersonal to cultural contexts, influence the psychological processes through which mindsets shape learning and resilience. This ecological system framework of mindset serves as a guide for future research to examine how to sustain learners’ growth in diverse sociocultural and achievement settings.